Substance activation member

The material activating member, composed of natural mineral powders, electron generating substances, and a cylindrical magnet body, addresses the limitations of conventional activating members by achieving a greater substance activation effect, enhancing combustion efficiency and material activation across various applications.

JP2025058901AInactive Publication Date: 2025-04-09LEPTON JAPAN LLC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024116749
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-07-22
Publication Date
2025-04-09
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional material activating members have limitations in achieving further enhanced material activating effects.

Method used

A material activating member comprising a powder of a natural mineral containing a radioactive material, a powder of an electron generating substance emitted from the natural mineral and generating electrons by alpha rays, and a cylindrical magnet body with specific pole configurations, filled with the activating material inside.

Benefits of technology

The solution enables a greater substance activation effect, improving combustion efficiency, exhaust gas cleaning, and enhancing the activation of various materials and fluids, leading to increased efficiency and performance in various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058901000001_ABST
    Figure 2025058901000001_ABST
Patent Text Reader

Abstract

To provide a substance activation member capable of exerting an improved activation effect on a substance.SOLUTION: A substance activation member comprises: a substance activation material that includes a powder body of a natural mineral containing a radioactive substance and a powder body of an electron generation substance for generating electrons by an alpha ray emitted from the natural mineral; and a cylindrical magnetic body which has an N-pole and an S-pole at one and the other end. The inside of the cylindrical magnetic body is filled with the substance activation material.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a material activating member. [Background technology]

[0002] In recent years, it has been proposed to activate substances such as the combustion air taken in by the engine and the combustion exhaust gas emitted by the engine, thereby reducing fuel consumption during high-speed driving and reducing the amount of carbon dioxide contained in the exhaust gas (for example, Patent Document 1).

[0003] Such material activation members generate radiation that ionizes the materials to be activated, such as the combustion air and combustion exhaust gas, and the electric charge generated during this ionization is charged to the metal layer that constitutes the metal layer, generating an electric field and a magnetic field. These electric field and magnetic field activate the target materials, thereby improving combustion efficiency and efficiently purifying exhaust gases. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-59909 A Summary of the Invention [Problem to be solved by the invention]

[0005] Although conventional substance activating materials exert a certain degree of excellent effect, there is a demand for the development of novel substance activating materials that exert an even greater substance activating effect.

[0006] The present invention has been made to solve such problems, and an object of the present invention is to provide a substance activating member capable of exerting a greater substance activating effect. [Means for solving the problem]

[0007] The above-mentioned object of the present invention is achieved by a material activation member comprising a material activation material having a powder of a natural mineral containing a radioactive substance and a powder of an electron generating material that is emitted from the natural mineral and generates electrons by alpha rays emitted from the natural mineral, and a cylindrical magnet body with a north pole at one end and a south pole at the other end, the inside of the cylindrical magnet body being filled with the material activation material.

[0008] Furthermore, with regard to this material activating member, it is preferable that the powder of the electron generating material contains a powder of titanium dioxide and at least one type of powder selected from lanthanum hexaboride, black silica, metallic magnesium, tungsten, metallic silicon, molybdenum disulfide, and metallic germanium.

[0009] It is also preferable that an electrode portion is connected to the one end of the cylindrical magnet body that is the north pole side.

[0010] The electrode portion is preferably a plate electrode connected to the entire end face of the one end of the magnet body.

[0011] It is also preferable that the plate electrode is formed so as to have an area larger than the area surrounded by the outer circumferential contour of one end of the magnet body. Effect of the Invention

[0012] According to the present invention, it is possible to provide a substance activating member capable of exerting a greater substance activating effect. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view of a substance activating member according to one embodiment of the present invention; [Diagram 2] 2 is a schematic cross-sectional view of a modified example of the substance activating member shown in FIG. 1. FIG. [Diagram 3] FIG. 11 is a schematic cross-sectional view of a substance activating member according to another embodiment of the present invention. [Figure 4]4 is a schematic plan view of the configuration as seen from the direction of the arrow A in FIG. 3. [Diagram 5] FIG. 4 is an explanatory diagram for explaining magnetic field lines of a cylindrical magnet body. [Figure 6] 4 is a schematic cross-sectional view of a modified example of the substance activating member shown in FIG. 3. FIG. [Figure 7] 13 is an image for explaining an experiment using a substance activating member according to the present invention. [Figure 8] 1 is a graph showing experimental results using a substance activating member according to the present invention. [Figure 9] 1 is a graph showing the results of an experiment confirming the effect of a substance activating member according to the present invention. [Figure 10] 1 is a graph showing the results of an experiment confirming the effect of a substance activating member according to the present invention. [Figure 11] 1 is a graph showing the results of an experiment confirming the effect of a substance activating member according to the present invention. [Figure 12] 1 is a graph showing the results of an experiment confirming the effect of a substance activating member according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes a material activating material according to one embodiment of the present invention. The present invention is not limited to the following embodiment, and can be modified as appropriate within the scope of the object of the present invention. The material activating material according to the present invention is a material capable of generating electrons, and is composed of a powder of a natural mineral containing a radioactive material, and a powder of an electron generating material that generates electrons by alpha rays emitted from the natural mineral. Needless to say, the powder of the natural mineral and the powder of the electron generating material are uniformly mixed.

[0015] Natural minerals containing radioactive substances are not particularly limited, and examples thereof include radium ore, beitouite, Bad Gastein ore, monazite, phosphate ore, columbite, tantalite, strobelite, pyrochlore, bastnasite, cerium concentrate, zircon, gomuite, davidite, brannellite, uraninite (pitchblende), ningyoite, uraninite, carnotite, tsjamunite, metachamunite, chayamunite, schrekingelite, zirkelite, xenotime, trogomuite, oerite, bakhanite, catullenite, tungstenite, botrylite, brockite, uranophene, lindourite, coffinite, uranium thorite, uranium botrylite, thorite, and fransevilleite.

[0016] As an electron generating material that generates electrons by alpha rays emitted from natural minerals, for example, titanium dioxide (TiO2) powder can be used.

[0017] The finer the average particle size of the powder of the natural mineral contained in the substance activation material according to the present invention, the greater the effect. For example, it is preferably set to 200 μm or less, more preferably set to 100 μm or less. Furthermore, it is more preferably set to 10 μm or less. Similarly, the finer the average particle size of the powder of the electron generating substance, the greater the effect. For example, it is preferably set to 200 μm or less, more preferably set to 100 μm or less. Furthermore, it is more preferably set to 10 μm or less.

[0018] In addition, with respect to the material activation material according to the present invention, the lower limit of the content of the natural ore is not particularly limited as long as it can generate a sufficient amount of alpha rays to activate the material to be activated. The lower limit of the content of the natural ore is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and particularly preferably 1 part by mass or more, relative to 100 parts by mass of the material activation material. In addition, the upper limit of the content of the natural ore is not particularly limited as long as it can reduce the amount of radiation generated to 0.2 μSv / h or less. The upper limit of the content of the natural ore is preferably 90 parts by mass or less, more preferably 85 parts by mass or less, and particularly preferably 80 parts by mass or less, relative to 100 parts by mass of the material activation material.

[0019] Moreover, with regard to the material activation material, the content of the electron generating material that is emitted from natural minerals and generates electrons by alpha rays is preferably set to a content that can maximize the ionization effect of alpha rays. In particular, the content of titanium dioxide contained in the electron generating material in the present invention is preferably set to, for example, 1 part by mass or more and 15 parts by mass or less with respect to 100 parts by mass of the material activation material. Moreover, the material activation material according to the present invention may be configured to have at least one powder selected from lanthanum hexaboride (LaB6), black silica, tungsten, metal silicon, molybdenum disulfide, metal germanium, gallium nitride (GaN), tourmaline, boron, and boron compounds as the electron generating material, in addition to titanium dioxide powder. Here, the content of lanthanum hexaboride is preferably set to 0.5 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the material activation material. Moreover, the content of black silica is preferably set to 1 part by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the material activation material. The content of tungsten is preferably set to 0.1 parts by mass or more and 0.5 parts by mass or less with respect to 100 parts by mass of the material activation material, and the content of metal silicon is preferably set to 2 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the material activation material. The content of molybdenum disulfide is preferably set to 2 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the material activation material, and the content of metal germanium is preferably set to 2 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the material activation material. The content of gallium nitride (GaN) is preferably set to 0.8 parts by mass or more and 2 parts by mass or less with respect to 100 parts by mass of the material activation material, and the content of tourmaline is preferably set to 2 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the material activation material. The content of boron is preferably set to 0.8 parts by mass or more and 2 parts by mass or less with respect to 100 parts by mass of the substance activating material, and the content of the boron compound is preferably set to 0.8 parts by mass or more and 2 parts by mass or less with respect to 100 parts by mass of the substance activating material. An example of the boron compound is disodium octaborate tetrahydrate.

[0020] The electron generating material may be configured to include metallic magnesium powder in addition to titanium dioxide powder. The average particle size of the metallic magnesium powder is preferably set to 0.3 mm to 1.5 mm, more preferably set to 0.5 mm to 1.0 mm. The content of the metallic magnesium powder is preferably set to 15 parts by mass to 35 parts by mass with respect to 100 parts by mass of the material activating material, and more preferably set to 20 parts by mass to 30 parts by mass with respect to 100 parts by mass of the material activating material. As described above, by setting the average particle size of the metallic magnesium powder to be significantly larger than the average particle size of the powder of the electron generating material, an extremely large amount of natural mineral powder comes into contact with one magnesium metal powder, making it possible to emit a much larger amount of electrons.

[0021] The electron generating material may be configured to contain copper powder in addition to titanium dioxide powder. The copper powder is preferably formed in a flake shape. The copper powder preferably has an average particle size of 10 μm or less, more preferably 1 μm or less. The copper powder has high conductivity, which allows efficient propagation to the outside. The content of the copper powder is preferably set to 1 part by mass or more and 4 parts by mass or less with respect to 100 parts by mass of the substance activating material.

[0022] In addition to titanium dioxide powder, the electron generating material may be configured to include powder in which the surface of copper powder is plated with silver (silver-plated copper powder). The powder in which the surface of copper powder is plated with silver is preferably formed in a flake shape. The average particle size of the powder in which the surface of copper powder is plated with silver is preferably 10 μm or less, more preferably 1 μm or less. The powder in which the surface of copper powder is plated with silver also emits electrons due to the bonding of dissimilar metals, silver and copper, so that the amount of electrons emitted is further increased. In addition, the powder in which the surface of copper powder is plated with silver has excellent conductivity, so that the electrons generated inside the electron generating material 52 can be efficiently propagated to the outside. The content of the powder in which the surface of copper powder is plated with silver is preferably set to 5 parts by mass or more and 20 parts by mass or less, and more preferably set to 8 parts by mass or more and 14 parts by mass or less, relative to 100 parts by mass of the substance activating material.

[0023] The electron generating material may be configured to include silver powder in addition to titanium dioxide powder. The silver powder is preferably formed in a flake shape. The average particle size of the silver powder is preferably 10 μm or less, and more preferably 1 μm or less. Since the silver powder has excellent conductivity, it is possible to efficiently propagate electrons generated inside the electron generating material 52 to the outside. The content of the silver powder is preferably set to 8 parts by mass or more and 12 parts by mass or less with respect to 100 parts by mass of the substance activating material.

[0024] The material activating material according to the present invention may further include a powder of a conductive carbon material such as graphite. The average particle size of the powder of the carbon material is preferably 10 μm or less, more preferably 1 μm or less. The content of the powder of the carbon material is preferably set to 1 part by mass or more and 5 parts by mass or less per 100 parts by mass of the material activating material. By further including such a powder of a conductive carbon material, the conductivity is further improved, and electrons can be efficiently propagated to the outside.

[0025] In addition, with respect to the material activating material according to the present invention, it is preferable to further mix a conductive fluid binder. Such a fluid binder is configured to include, for example, a powder of a metal material and a solvent. This fluid binder may be a dry type that dries naturally, or a non-drying type that does not dry naturally. When the fluid binder is configured as a dry type, for example, a solvent that volatilizes by natural drying is used. When the fluid binder is configured as a non-drying type, for example, a non-drying oil such as non-drying grease or a mineral oil can be used as the solvent. The average particle size of the powder of the metal material contained in the fluid binder is preferably 200 μm or less.

[0026] By mixing the fluid binder to form the material activation material, the powder of the natural ore and the powder of the electron-generating material contained in the material activation material can be maintained in a uniformly dispersed state. In addition, when a dry fluid binder is used, for example, the material activation material having fluidity is poured into a specified mold, and then dried, so that the solvent contained in the fluid binder evaporates, and as a result, the material activation material can be molded and solidified to a desired shape. In addition, when a non-drying fluid binder is used, it is possible to configure the material activation material to have fluidity.

[0027] Here, the conductive metal material contained in the flowable binder is preferably at least one selected from zinc, molybdenum disulfide, and copper. In addition, a suitable example of the flowable binder containing zinc powder is a room temperature plating paint containing zinc. This room temperature plating paint containing zinc is suitable for forming and solidifying a material activation material to a desired shape because the solvent contained in the paint evaporates at room temperature and the zinc solidifies after evaporation. In addition, zinc is also a material that generates electrons by alpha rays emitted from natural minerals, so that the material activation material formed and solidified from the material activation material generates electrons from the electron generating material and zinc by alpha rays emitted from natural minerals, so the amount of electrons emitted increases. In addition, zinc is conductive, so that electrons generated inside the material activation material can be efficiently propagated to the outside of the material activation material.

[0028] As a fluid binder containing molybdenum disulfide powder, for example, molybdenum disulfide grease can be preferably used. This molybdenum disulfide grease is a mixture of non-drying grease and molybdenum disulfide powder, so the material activation material maintains its fluidity without being naturally dried. Such a material activation material containing molybdenum disulfide grease as a fluid binder can be used by attaching it to the tip of a screw part to be removed. Note that molybdenum disulfide is also a material that generates electrons by alpha rays emitted from natural minerals. Note that copper grease, which is a mixture of non-drying grease and copper powder, can also be preferably used.

[0029] In addition, the content of the fluid binder in the material activation material is preferably, for example, 50 parts by mass or more and 75 parts by mass or less relative to 100 parts by mass of the material activation material. When a dry fluid binder is used, the content is not particularly limited to the above numerical range, as long as it can maintain the shape when the solvent evaporates and the material activation material evaporates and dries, for example, the shape in the dry state when a fluid material activation material is applied and dried, or the shape when a fluid material activation material is poured into a specified mold and then dried to form the material activation material into a desired shape. In addition, when a non-drying fluid binder is used, the content is not particularly limited to the above numerical range, as long as the material activation material has fluidity.

[0030] Regarding the flowable binder, the higher the content of the powder of the metal material, the better. When a dry flowable binder is used, the content is sufficient as long as it can maintain the shape when the solvent evaporates and the binder is dried, for example, the shape in the dry state when a flowable substance activation material is applied and dried, or the shape when the flowable substance activation material is poured into a predetermined mold and then dried to form the substance activation material into a desired shape. When a non-drying flowable binder is used, the content is not particularly limited as long as the substance activation material has flowability.

[0031] Next, the substance activating member 1 according to the present invention will be described with reference to the attached drawings. The present invention is not limited to the following embodiments, and can be modified as appropriate within the scope of the object of the present invention. Each drawing is partially enlarged or reduced in size to facilitate understanding of the configuration. The substance activating member 1 according to the present invention is a member made using the above-mentioned substance activating material, and includes, for example, an electron generating section 2 and an electrode section 3, as shown in the schematic cross-sectional view of FIG. 1.

[0032] The electron generating unit 2 is configured to include a powder of a natural mineral containing a radioactive substance, and a powder of an electron generating material that generates electrons by alpha rays emitted from the natural mineral.

[0033] As with the above, examples of natural minerals containing radioactive substances include radium ore, beitouite, Bad Gastein ore, monazite, phosphate ore, columbite, tantalite, strobelite, pyrochlore, bastnasite, cerium concentrate, zircon, gomuite, davidite, brandnerite, uraninite (pitchblende), ningyoite, uraninite, carnotite, tsjamunite, metachamunite, chayamunite, schreckingerite, zirkelite, xenotime, trogomuite, oerite, bakhanite, catullenite, tungstenite, botrylite, brockite, uranophene, lindourite, coffinite, uranium thorite, uranium botrylite, thorite, and fransevilleite.

[0034] Furthermore, examples of electron generating substances that generate electrons by alpha rays emitted from natural minerals include, as described above, a mixture of titanium dioxide (TiO2) powder and at least one powder selected from lanthanum hexaboride (LaB6), black silica, metallic magnesium, copper, silver-plated copper, silver, tungsten, metallic silicon, molybdenum disulfide, metallic germanium, gallium nitride (GaN), tourmaline, boron, and boron compounds.

[0035] The average particle size of the powder of the natural mineral is, for example, preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 10 μm or less. The average particle size of the powder of the electron generating material is, for example, preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 10 μm or less.

[0036] The electron generating unit 2 can be formed, for example, by mixing a powder of a natural mineral containing radioactive substances and a powder of an electron generating material that is emitted from the natural mineral and generates electrons by alpha rays with a conductive fluid binder and stirring the mixture uniformly to form a fluid material activation material, which is then applied to a sheet-like electrode unit 3 in a predetermined thickness to form the electron generating unit 2, and then stacking another sheet-like electrode unit 3 on top and drying.

[0037] A suitable example of the fluid binder is a cold plating paint containing zinc. The cold plating paint containing zinc contains a solvent that volatilizes at room temperature, and the zinc solidifies after volatilization, allowing the substance activation material to be molded and solidified into a desired shape.

[0038] Here, the electrode unit 3 is a member that is electrically connected to the target of substance activation, and the material thereof is not particularly limited as long as it can transmit the electrons generated by the electron generating unit 2 to the target of substance activation. However, it is preferable to use a material with high electrical conductivity such as copper, silver, or gold, and it is more preferable to use copper from a cost perspective.

[0039] Here, the structure of the material activating member 1 shown in FIG. 1 is a sheet-shaped material activating member 1 having a single layer of electron generating section 2, but is not limited to such a structure. As shown in the schematic cross-sectional structure diagram of FIG. 2, the material activating member 1 may be a multi-layer type material activating member in which sheet-shaped electron generating sections 2 and sheet-shaped electrode sections 3 are alternately laminated. Furthermore, although the material activation member 1 shown in FIG. 1 has a sheet-like configuration, it is not particularly limited to this form, and it goes without saying that the material activation member 1 can be configured in various shapes (for example, cylindrical, rectangular, bolt-shaped, box-shaped, curved, etc.) by pouring a fluid material activation material into a specified mold and then drying it to remove the solvent contained in the fluid binder.

[0040] Furthermore, as the material activation member 1, a configuration can be adopted in which the above-mentioned material activation material is filled inside a cylindrical magnet body 4 to form an electron generating section 2, and an electrode section 3 is connected to the magnet body 4, as shown in the schematic cross-sectional view of FIG. 3 and in FIG. 4, which is a plan view seen from the direction of arrow A in FIG. 3.

[0041] The magnet body 4 is configured as a cylindrical magnet body 4 with one end being an N pole and the other end being an S pole. The electrode unit 3 is not particularly limited as long as it is configured to connect to the magnet body 4, but it is preferable that an electrode is connected to one end on the N pole side of the cylindrical magnet body 4, and it is particularly preferable that the electrode is configured as a plate electrode in which the entire end face of one end on the N pole side of the magnetic body 4 is connected and the opening on the one end side of the cylindrical magnet body 4 is closed, as shown in Figs. 3 and 4. It is more preferable that the plate electrode is formed to have an area larger than the area surrounded by the outer circumferential contour of one end of the cylindrical magnet body 4.

[0042] Here, the substance activation material filled inside the cylindrical magnet body 4 may comprise only a powder of a natural mineral containing a radioactive substance and a powder of an electron generating substance that generates electrons by alpha rays emitted from the natural mineral, or may further contain a conductive fluid binder. The fluid binder may be either dry or non-drying.

[0043] In this way, the material activation member 1 formed by filling the inside of a cylindrical magnet body 4 with a material activation material has the electrons generated in the material activation material moving at an increased speed due to the magnetic field lines of the magnet body 4, and the direction of movement is controlled by the magnetic field lines, making it possible to transmit electrons at high speed to the material activation target.

[0044] In addition, as shown in FIG. 5, the magnetic field lines of the magnet body 4 leave the N-pole side and enter the S-pole side, so that the electrode unit 3 is connected to one end on the N-pole side, it is possible to efficiently guide the electrons generated in the electron generating unit 2 to the electrode and propagate them to the material activation target. In particular, as shown in FIG. 3 and FIG. 4, it is preferable to adopt a plate electrode to which the entire end face of one end on the N-pole side of the magnet body 4 is connected, from the viewpoint of efficiently propagating the electrons generated in the electron generating unit 2 to the material activation target. Furthermore, by forming the plate electrode to have an area larger than the area surrounded by the outer circumferential contour of one end of the cylindrical magnet body 4, it is possible to propagate the electrons moving along the magnetic field lines formed on the outside of the magnet body 4 to the material activation target via the plate electrode. In other words, it is possible to efficiently propagate the electrons emitted toward the outside of the magnet body 4 to the material activation target.

[0045] As shown in the schematic cross-sectional view of FIG. 6, the magnet body 4 may be configured to include an insulating member 5 that covers the side portion and the other end side. There is no particular limitation on the material for forming the insulating member 5, and any commonly known insulating material may be used. The insulating member 5 may be removable, such as a rubber cap, or may be fixed to cover the surface of the magnet body 4 with an insulating resin material so that it cannot be removed. By including such an insulating member 5, it is possible to effectively prevent the electrons generated in the electron generating unit 2 from being emitted outside the material activation member 1, and to effectively propagate the generated electrons toward the material activation target.

[0046] The material activating member 1 having such a configuration can be attached to a device in which a material to be activated is present in various fields, thereby effectively activating the material. For example, the sheet-shaped material activating member 1 is wrapped so as to be in close contact with the surface of an air duct of an automobile engine, and fixed with a fastener such as a cable tie, whereby electrons generated from the material activating member 1 are transmitted to the air molecules of the intake air flowing inside the air duct, and the activation of the air molecules is greatly promoted. When the intake air thus activated is supplied to the inside of the cylinder of the automobile engine, the fuel injected into the cylinder and the activated intake air are sufficiently mixed, so that the combustion efficiency of the fuel in the cylinder is greatly improved, and the fuel consumption rate can be reduced and the purification of the exhaust gas can be promoted. In addition, since the material activating member 1 is attached to the outside of the air duct, it does not become a resistance when the engine takes in air.

[0047] Furthermore, by wrapping the material activating member 1 around the outside of an automobile exhaust pipe, the electrons emitted from the material activating member 1 are transmitted to compounds such as carbon monoxide, carbon dioxide, and nitrogen oxides contained in the exhaust gas, greatly accelerating the activation of these compounds, and these compounds are sent to the catalytic device in a state that is significantly activated by the transmitted electrons, allowing for extremely efficient purification. Furthermore, because the material activating member 1 is wrapped around the outside of an automobile exhaust pipe, it will not be damaged by the effects of high-temperature exhaust gas.

[0048] Furthermore, by wrapping the material activating member 1 around the outside of the cylinder block of an automobile, the electrons emitted from the material activating member 1 act on the intake air or exhaust gas of the automobile engine flowing inside the cylinder block, greatly promoting their activation. The intake air or exhaust gas is sent to the catalyst device in a state that is greatly activated by the propagated electrons, and is therefore purified extremely efficiently.

[0049] The material activating member 1 can also be used in a lubrication system that lubricates the sliding parts of a machine with lubricating oil. Lubricating oil is used to reduce friction between metal parts of a machine that slide against each other, but such lubricating oil is affected by heat, worn metal powder, etc., and its lubricating ability and heat exchange ability gradually decrease. In addition, if metal wear powder accumulates on an oil filter, the passage ability of the lubricating oil decreases, and the lubricating performance further decreases. Therefore, by wrapping the material activating member 1 around a container that stores the lubricating oil that lubricates the sliding parts of a machine, or around the outside of a tube through which the lubricating oil flows, the electrons emitted from the material activating member 1 act on the lubricating oil flowing inside the lubricating device, greatly promoting the activation of the lubricating oil. The lubricating oil that has been activated by the electrons propagating therethrough can flow smoothly between the metal wear powder, etc., accumulated on the oil filter, so that not only can the lubricating performance be improved while maintaining the performance of the oil filter, but also the load on the oil pump can be reduced to reduce power loss.

[0050] The material activating member 1 can also be used in a cooling device that uses a coolant to cool the heat-generating parts of a machine. For example, in an engine, the coolant is pressurized and circulated to efficiently remove heat generated by combustion from the cylinder block. However, circulating the coolant under pressure not only places a burden on the pump, but also causes leakage from pipe connections and damage to hoses. Therefore, by wrapping the material activating member 1 around a container that stores the coolant that cools the heat-generating parts of a machine, or around the outside of a tube through which the coolant flows, the electrons emitted from the material activating member 1 act on the coolant flowing inside the cooling device, greatly promoting the activation of the coolant. This allows a coating to be formed on the inner wall surface of the coolant circulation system, which not only improves the heat transfer rate and improves the cooling efficiency, but also causes the coolant to flow smoothly as a laminar flow, reducing the circulation resistance of the coolant. As a result, the circulation pressure of the coolant can be reduced, which not only reduces the burden on the pump and reduces power loss, but also prevents leakage from pipe connections and damage to hoses. Furthermore, the layer of coolant in which electrons are propagated and activated has the effect of preventing corrosion of the coolant circulation system and also preventing deterioration of rubber hoses and the like.

[0051] The material activating member 1 can also be used in a fuel supply device that supplies liquid or gaseous fuel to a combustion engine such as an engine. In general combustion, vaporized liquid or gaseous fuel is combined with oxygen in a combustion chamber to extract thermal energy. In order to efficiently extract the energy from the liquid or gaseous fuel, the fuel and air must be mixed thoroughly. Therefore, by wrapping the material activating member 1 around the outside of a container that contains the liquid or gaseous fuel to be supplied to the combustion engine, or a pipe through which the fuel flows, electrons generated from the material activating member 1 act on the fuel, greatly promoting the activation of the fuel. This makes it possible to make the particle size of the fuel much finer when the fuel is atomized by being injected from a fuel injection valve than in the normal case. As a result, the fuel and air can be mixed thoroughly in the combustion chamber, and the thermal energy of the fuel can be extracted sufficiently. This can be applied not only to gasoline but also to all petroleums that contribute to combustion.

[0052] The material activation member 1 can also be used for the moving blades that make up a turbine. In hydroelectric power generation, water, in thermal power generation, steam, in automobile automatic transmissions, and other working fluids such as oil are applied to the turbine blades to obtain rotational driving force. However, when the fluid comes into contact with the turbine blades, the resistance generated in the turbine blades increases as the fluid speed increases, so if the fluid speed is increased too much, it leads to a decrease in the energy transmission capacity from the fluid to the turbine blades. Therefore, by wrapping the material activation member 1 around the outside of the turbine blades or the outside of the casing that houses the turbine blades inside, electrons generated from the material activation member 1 act on the above-mentioned fluid, greatly promoting the activation of the fluid. This forms a laminar flow on the surface of the turbine moving blades, allowing the fluid to flow smoothly between the turbine blades, reducing the resistance generated in the turbine blades and making it possible to obtain rotational driving force with high efficiency.

[0053] The material activating member 1 can also be used in cooling devices such as air conditioners. Cooling devices such as air conditioners and refrigerators evaporate a refrigerant in an evaporator to remove heat from the air in a room or refrigerator, compress the refrigerant in a condenser, and release the heat to the outside through a radiator. Therefore, in order to improve the cooling performance of refrigerators and air conditioners, it is necessary to improve the heat exchange efficiency of the refrigerant in the evaporator. Therefore, by wrapping the material activating member 1 around an evaporator, which is a passage for the refrigerant used in the cooling device, or a pipe through which the refrigerant flows inside the evaporator, electrons generated from the material activating member 1 act on the refrigerant, greatly promoting the activation of the refrigerant. As a result, a film of the activated refrigerant adheres closely to the metal inner wall surface of the evaporator or pipe, and the heat exchange efficiency between the refrigerant and the metal inner wall surface of the evaporator or pipe can be greatly improved.

[0054] The material activating member 1 can also be used in a cleaning water storage container. In general households, tap water is used as a solvent for detergents used to wash dishes, etc. Hot water must be used to increase cleaning power, which is problematic as it increases utility costs. Therefore, by wrapping the material activating member 1 around a cleaning water storage container or a pipe through which cleaning water flows, electrons generated from the material activating member 1 act on the fluid, greatly promoting the activation of the cleaning water. When activated tap water through which electrons have been propagated is used as a solvent, the detergent surfactant efficiently exhibits an activating effect even at room temperature. As a result, the ability to clean dishes, laundry, etc. can be greatly improved. Incidentally, activated tap water through which electrons have been propagated also has the effect of preventing corrosion inside water pipes.

[0055] The material activating member 1 can also be used for plant growth. In addition to sunlight and carbon dioxide in the atmosphere, plants need water containing nutrients to grow. In order to promote plant growth, it is preferable to increase the amount of water absorbed by the roots of the plants. One method for doing so is to increase the temperature of the water, but this method only increases the amount of water absorbed by the roots of the plants to a certain extent. In order to increase the amount of water absorbed by the roots of the plants, the material activating member 1 is wrapped around a supply water storage container for water containing nutrients to be supplied to the plants, or around a pipe through which the supply water flows, so that electrons generated from the material activating member 1 act on the above-mentioned fluid, greatly promoting the activation of the supply water, etc. This makes it possible to activate the water to be supplied to the plants and the nutrients contained therein, and the water and nutrients thus activated are easily absorbed by the hair roots of the plants, thereby promoting the growth of the plants. Nitrogen compounds required by plants are produced when bacteria and enzymes decompose leaf mold, and supplying highly activated water promotes the decomposition of leaf mold and increases the production of nitrogen compounds. This makes it possible to significantly promote plant growth by using activated water containing a sufficient amount of dissolved nitrogen compounds.

[0056] The material activating member 1 can also be used for the growth of animals. Animals need water to grow, as it constitutes most of their bodies. Animals kept in zoos and other facilities obtain their drinking water from tap water. However, while the drinking water is stored in a supply water tank, oxidation and deterioration of the drinking water progresses. Therefore, by wrapping the material activating member 1 around the outside of the supply water tank or the inside of the tank, electrons generated from the material activating member 1 act on the supply water to activate it. The activated water is easily absorbed into the animal's body. In addition, the material activating member 1 has an antioxidant effect to suppress the redox potential, and is also effective in enhancing immune function and promoting growth.

[0057] The material activating member 1 can also be used for growing fish and shellfish. Since fish and shellfish live in water, the quality of the water is extremely important. When raising fish and shellfish, waste products are discharged into the same tank as the water they live in, so if the water is not constantly purified, the quality of the water will deteriorate. Therefore, by wrapping the material activating member 1 around the outside of a supply water storage container for water supplied to fish and shellfish, a circulating purification device, or the inside of the device around the outside of a pipe through which the supply water flows, electrons generated from the material activating member 1 act on the supply water to activate it. The activated water is then easily absorbed into the body of the fish and shellfish. In addition, the material activating member 1 has an antioxidant effect to suppress the redox potential, and is also effective in enhancing immune function and promoting growth.

[0058] The material activating member 1 can also be used in a septic tank that treats wastewater. In a septic tank that treats human waste discharged from a general household, aerobic bacteria oxidize and decompose organic substances while taking in oxygen from the air. Therefore, by multiplying such aerobic bacteria, it becomes possible to efficiently treat human waste. Therefore, by wrapping the material activating member 1 around an aeration air supply pump or the inside of the pump around the outside of a pipe through which air for aeration flows, electrons generated from the material activating member 1 act on the air passing through the pump or the air flowing through the pipe, activating the air. As a result, activated air can be supplied to the septic tank, activating the aerobic bacteria that decompose human waste and treating the wastewater more efficiently.

[0059] The material activating member 1 can also be used in a spray painting device. When painting the body of an automobile, in order to form a more uniform and high-quality painted surface, it is necessary to make the particle size of the paint dispersed in mist smaller. However, since conventional spray painting devices are structured to disperse the paint in mist using air as is, it is difficult to further reduce the particle size of the dispersed paint. Therefore, by wrapping the material activating member 1 around the compressed air supply pump used to spray and atomize the paint, or the outside of the pipe through which the compressed air flows inside the pump, electrons generated from the material activating member 1 act on the air passing through the pump or the air flowing through the pipe, activating the air, and spraying and atomizing the paint using the activated compressed air, the mixing of the air and the paint is promoted, and the particle size of the atomized paint can be made even smaller. Therefore, a more uniform and high-quality painted surface can be formed.

[0060] It has also been confirmed that by allowing the electrons emitted from the material activating member 1 to act on a fluid (gas, liquid, powder, etc.) moving through a tube, the flow rate of the fluid increases, improving the transfer efficiency. For example, it is possible to shorten the time it takes to transfer powder from a tank truck through piping to a factory tank. This is thought to be because the addition of electrons removes static electricity and reduces frictional resistance between the powder and the piping, thereby increasing the flow rate. In addition, by wrapping the material activating member 1 around the outside of an automobile exhaust pipe, for example, the exhaust rate of the exhaust gas increases, allowing it to escape more easily from the exhaust pipe, improving the combustion efficiency of the engine.

[0061] The inventors conducted an experiment to confirm the effect of the material activating member according to the present invention, which will be described below. First, the material activating member used in the experiment was created as shown in FIG. 1, and was formed into a rectangular parallelepiped shape with a thickness of 10 mm and a length x width of 40 mm x 60 mm. The electron generating portion (material activating material) was formed by mixing a powder of radium ore (natural ore), a powder of an electron generating material, and a room temperature plating liquid containing zinc (a conductive fluid binder; a room temperature plating paint containing 96% zinc) and thoroughly stirring the mixture, pouring the mixture into a mold, drying the mixture, and removing the mixture from the mold. Then, electrode portions (length x width = 40 mm x 60 mm) made of copper and having a thickness of 0.02 mm were laminated on both sides of the mixture. In addition, lead wires were connected to the copper electrode portions arranged on both sides of the material activating member, and plate-shaped terminal portions were connected to the tips of the lead wires, so that the electrons generated in the material activating member were propagated from the terminal portions to the activation target. The content of radium ore (natural ore) was 2 parts by mass relative to 100 parts by mass of the material activation material, the content of the electron generating material was 22.3 parts by mass relative to 100 parts by mass of the material activation material, and the content of the fluid binder was 75.7 parts by mass relative to 100 parts by mass of the material activation material. As the electron generating material, a powder mixture of titanium dioxide, metallic magnesium, metallic silicon, black silica, lanthanum hexaboride, copper, and metallic germanium was used. The content of titanium dioxide powder was 8 parts by mass relative to 100 parts by mass of the material activation material, the content of metallic magnesium powder was 7.3 parts by mass relative to 100 parts by mass of the material activation material, the content of metallic silicon was 3 parts by mass relative to 100 parts by mass of the material activation material, and the content of black silica was 2 parts by mass relative to 100 parts by mass of the material activation material. The content of lanthanum hexaboride was 0.5 parts by mass relative to 100 parts by mass of the substance activating material, and the content of copper powder was 2 parts by mass relative to 100 parts by mass of the substance activating material. It was confirmed that when the terminal portion of the material activating member thus formed was connected to the high-pressure side pipe of the refrigerant gas of an air conditioner and electrons were applied, the temperature of the air outlet during cooling was reduced by 1 to 4°C, as shown in FIG. 7. Specifically, the temperature was measured 20 minutes after the air conditioner was turned on when the material activating member was used and when it was not used. The temperature was measured at the high-pressure side surface and low-pressure side surface of the refrigerant gas pipe and the indoor outlet. When the material activating member was not used, the temperatures of the high-pressure side and low-pressure side of the refrigerant gas pipe were 17.5°C and 22.7°C, respectively, and the temperature of the indoor outlet was 14.8°C. On the other hand, when the material activating member was used, the temperatures of the high-pressure side and low-pressure side of the refrigerant gas pipe were 15.5°C and 22.0°C, respectively, and the temperature of the indoor outlet was 11.6°C, and it was found that the temperature of the indoor outlet was reduced by 3.2°C by using the material activating member. In this experiment, the room temperature was 29.5°C, and the air conditioner was set to an energy-saving setting of 28°C. It was also confirmed that the lubricating effect reduced noise levels. These findings suggest that electricity can be reduced by controlling the temperature settings. In electrical appliances in general, adding electrons to the device improves thermal conductivity, improves the flow of electricity, and increases efficiency, and reduces frictional resistance, contributing to reduced electricity bills. The flow of electricity depends on the state of the free electrons in the conductor, and it is thought that adding electrons to the refrigerant slightly reduces the resistance. In addition to air conditioners, it has also been confirmed that adding electrons to the refrigerant in freezers and, mainly, household refrigerators, improves their cooling capacity. Next, an experiment was conducted in which the terminals of the material activating material used in the experiment were connected to the motor of an electric fan and electrons were added. Specifically, first, the change in the sound of the motor was measured when the material activating material was used and when it was not used. As a result, it was confirmed that the motor sound level was reduced, mainly at 54 Hz, by 3.7 dB, from -50.0 dB to -46.3 dB, when the material activating material was used. This confirmed that the burden on the motor, that is, the frictional resistance of the motor itself, was reduced when the material activating material was used. It was also confirmed that the wind noise of the fan blades was reduced. This is because the loop in which static electricity is generated by friction with the air when the resin blades rotate, and further frictional resistance is generated by charging, was broken by the material activating material removing the static electricity, and as a result, the frictional resistance (mainly frictional resistance generated by static electricity) associated with the rotation of the blades was reduced.

[0062] It was also confirmed that the thermal conductivity of water was improved by providing water with electrons emitted from the material activating member 1. Specifically, ordinary tap water and tap water to which electrons were provided by the material activating member were prepared, and the change in water temperature over time (heating time) when heated under the same conditions was measured for each. The measurement results are shown in Table 1 below, and the graph is shown in FIG. 8. From Table 1 and the graph in FIG. 8, it can be seen that the tap water to which electrons were provided by the material activating member was heated more efficiently, and that the thermal conductivity of water was improved by the provision of electrons. In particular, it was confirmed that the thermal conductivity at 40 to 60°C was improved by nearly 40% compared to water to which electrons were not provided. By improving the thermal conductivity of water in this way, the penetration power increases, the extraction power of cooked foods improves, and it is also possible to penetrate quickly. Furthermore, the penetration effect on plants has also been confirmed, and it has been confirmed that if harvested vegetables are soaked in water to which electrons have been provided, the water penetrates the plants and keeps them fresh. In addition, when oil is added to water and stirred, and the separation state is checked between normal water and water that has been given electrons, it is found that the normal water separates more quickly, which indicates that the affinity with oil is improved.

[0063] [Table 1] It was also confirmed that when electrons emitted from the material activating member 1 are applied to a metal cutting machine, cutting is performed more smoothly and the cutting accuracy of the processed surface is improved. Normally, when lubricating oil is not used, metal-to-metal contact causes seizure. For this reason, lubricating oil is used to reduce friction by using a film of lubricating oil to prevent direct contact between metals, but it was confirmed that by applying electrons instead of lubricating oil, frictional resistance is reduced even when metals come into contact with each other, making seizure less likely to occur.

[0064] In addition, manufacturers usually recommend replacing car batteries every three years or after 30,000 km of driving, because the maximum capacity of the battery decreases. In the case of a battery whose maximum capacity has decreased to 80%, even if it is fully charged, it can only be charged to 80%. However, by adding a few mL of organic germanium solution to each cell of the battery to which electrons released from the material activating material 1 have been added, the maximum capacity of the battery can be restored to 100% by simply driving normally for a few days, even if the battery capacity has decreased to 80%. In addition, the effect of extending the discharge time of a lithium-ion battery was also confirmed for the same battery. This naturally varies depending on the current value, but it is possible to extend the discharge time by 20 to 30% when used at the rated current of the battery. It was also confirmed that when charging a lithium-ion battery, if electrons are introduced from the negative terminal through the material activating material 1, the capacity of the old battery that has decreased in capacity gradually increases.

[0065] In addition, the following two batteries were prepared as automotive batteries and a battery revival test was conducted. Battery 1: A battery that had been replaced after being dead and then left unused. Battery 2: Battery that can be used without any problems Battery 1 has a no-load voltage of 8.8V, which is 5V when connected to a charger, falling below the standard 7.4V and making it impossible to recover by charging. Battery 2 has a no-load voltage of 12.2V and can be charged normally without any problems.

[0066] The battery fluid that had supplied electrons to Battery 1 and Battery 2 was injected up to the electrolyte standard level (5cc per cell) and charged. Battery 1 was in a state where it could not be charged because the charger circuit was not working, and Battery 2 was fully charged in 7 hours of normal charging. Battery 1 had been left in a dead state for six months, so the sulfation on the electrodes had crystallized and it was in an unrecoverable state where no current flowed at all. Therefore, Battery 2 was connected in parallel to Battery 1, the voltage was increased to 10V or more at which the charger operates, the charging circuit was operated, and Battery 2 was immediately removed. As a result, although the charging circuit worked, the battery electrodes of Battery 1 were damaged and no current flowed at all, so there was no change in the state where it could not be charged. However, after repeating this state several times, suddenly the current started to flow and it became possible to charge. Five hours later, when the battery was about 40% charged, bubbles started to bubble out of the electrolyte cap and the electrolyte inside overflowed. In total, nearly 20cc spilled out. Before adding the battery electrolyte, the electrolyte level was above the upper level, so the electrolyte was drained to adjust the level. However, the electrolyte was clear and colorless, whereas the overflowing electrolyte contained black particles and was generally blackish. Battery 1 was then fully charged in 4 hours.

[0067] This battery 1 was installed in a Daihatsu Move, and an engine start test was performed. It was confirmed that the engine started smoothly when the ignition key was turned. After that, the engine was turned off, the power window was opened and closed, and the engine was started again. This was repeated four times, and it was confirmed that the engine started without any problems. In addition, it is said that a battery that has been over-discharged (a state in which the battery has dropped to 10V due to a dead battery, etc.) is unable to fully recover even if it is charged, because the electrodes are covered with sulfation, and it is almost impossible for the sulfation to melt when it is charged, especially for a battery that has fallen below 7.4V, because the sulfation crystallizes, and it is almost impossible for the sulfation to melt when it is charged. It is said that if the electrodes are left covered with the crystallized sulfation for six months, it is absolutely impossible to regenerate the battery. However, it was confirmed that even such a battery can be revived without any problems by using the material activating member according to the present invention. After the above test, we conducted a battery implementation test for one week, and found that there were no problems even when driving with the air conditioner on all the time, half day and half night.The engine started very well, and there was no noticeable dimming of the headlights even when idling.

[0068] In addition, using a Delica D5 manufactured by Mitsubishi Motors Corporation, the change in engine sound during climbing was measured when the material activating member was attached to the engine and when it was not attached. The measurement results are shown in Figures 9 and 10. The measurement results when the material activating member was not attached to the engine are shown in Figure 9, and the measurement results when the material activating member was attached to the engine are shown in Figure 10. The noise level when the material activating member was not attached to the engine was 60.7 dB, while the noise level when the material activating member was attached to the engine was 48.7 dB, which shows a 12 dB reduction in noise level. The measurement results regarding frequency distribution are shown in Figures 11 and 12. The measurement results when the material activating member was not attached to the engine are shown in Figure 11, and the measurement results when the material activating member was attached to the engine are shown in Figure 12. From Figures 11 and 12, it can be seen that the engine sound in the low range below 150 Hz is reduced.

[0069] In addition, by applying electrons to chicken eggs when they hatch, the utilization rate of the egg yolk at the time of hatching is close to 100%, and blood tests on chicks have confirmed that the spleen immune index mRNA value has increased and that their weight has increased above the standard value. It is believed to have a large effect on the chick's dorsal hemagglutination antibody titer and spleen immune-related gene expression. In the case of humans, it has been confirmed using a blood flow microscope that the blood flow to the fingertips increases in just 10 seconds when electrons are applied to the ankle, and that the surface temperature of the back of the hand increases by 2 to 4 degrees Celsius in an average of several tens of minutes.

[0070] Furthermore, the inventors conducted an experiment to confirm the effect of a non-drying substance activating material that does not dry naturally, which will be described below. First, four types of non-drying substance activating materials were prepared for the experiment (Sample 1 to Sample 4). The content of each material contained in each non-drying substance activating material is shown in Table 2.

[0071] [Table 2] Here, the molybdenum disulfide paste used was a fluid binder, containing a mineral oil as a base oil and molybdenum disulfide powder with an average particle size of 1 μm. For Samples 1 and 2, the molybdenum disulfide powder content in the molybdenum disulfide paste was 30 parts by mass relative to 100 parts by mass of the molybdenum disulfide paste, and for Samples 3 and 4, the molybdenum disulfide powder content in the molybdenum disulfide paste was 50 parts by mass relative to 100 parts by mass of the molybdenum disulfide paste. The titanium dioxide powder, metal silicon powder, black silica powder, copper powder, lanthanum hexaboride (LaB6) powder, gallium nitride (GaN) powder, and tourmaline powder all had average particle sizes of 1 μm or less.

[0072] The non-drying substance activating material for each sample was applied to the capacitors and transistors of an audio device (DENON's CD player: DCD-1650AR), and a sensitivity test was conducted to see whether or not multiple people (10 people) felt any change in the sound by listening to the music played from the audio device. In addition, a sensitivity test was also conducted without the non-drying substance activating material. As a result, when the non-drying substance activating material for each sample was applied, the sound was evaluated as being more transparent and more realistic and vivid than when it was not applied. This effect is thought to be due to the electrons released from the non-drying substance activating material and propagated to the audio device reducing the mechanical noise emitted by the audio device and the noise coming in from the power source.

[0073] In addition, the results showed that the sound transparency was greater when sample 2 was applied than when sample 1 was applied. This is believed to be the effect of increasing the titanium dioxide content and including gallium nitride. In addition, the results showed that the sound quality was better, and the sound transparency and realism were greater when sample 3 was applied than when sample 2 was applied. This is believed to be largely due to the effect of increasing the content of molybdenum disulfide powder in the molybdenum disulfide paste and improving conductivity. It is also believed to be the effect of including lanthanum hexaboride powder. In addition, the results showed that the sound quality was significantly better when sample 4 was applied than when sample 3 was applied, the sound transparency and realism were greater, and the quietness in quiet parts of the music where no sound was playing was also good. This is believed to be the effect of increasing the content of titanium dioxide.

[0074] The inventor also confirmed whether there was a change in the machining accuracy and the operating sound of the machine by applying the non-drying substance activating material according to Samples 1 to 4 to the power supply-related device of a milling machine that rotates a blade to cut metals and the like. As a result, it was confirmed that when the non-drying substance activating material according to each sample was applied, the machining accuracy was improved and the operating sound of the machine was quieter than when it was not applied. This is considered to be an effect obtained by reducing the frictional resistance between the blade and the workpiece due to the action of electrons released from the non-drying substance activating material and propagated to the milling machine, resulting in a reduction in the vibration of the rotating blade. It was also confirmed that the above effect was greater in Sample 2 than in Sample 1, and greater in Sample 3 than in Sample 2, and furthermore, it was confirmed that the effect was expressed even more greatly in Sample 4 than in Sample 3.

[0075] In addition, the inventor applied the non-drying substance activating material according to Sample 1 to the fixed capacitor of the mother board of a tower-type personal computer (OS: Windows 10) that he built 15 years ago, and performed a confirmation test on the change in the start-up time of the personal computer. As a result of this confirmation test, it was confirmed that the start-up time changed from 25 seconds before application to 15 seconds after application. The application position of the non-drying substance activating material for the fixed capacitor is the electrode part of the capacitor on the back side of the printed circuit board. Furthermore, as a result of applying the non-drying substance activating material according to Sample 1 to the solid capacitor near the CPU fan and memory of the personal computer, it was confirmed that quietness and perceived speed were improved. From this result, it can be seen that the electron generating paste according to the present invention can improve the operating speed and quietness of the computer. [Explanation of symbols]

[0076] 1 Material activation component 2. Electron Generator 3 Electrode part 4. Magnet body 5. Insulating materials

Claims

1. A substance activation material including a powder of a natural mineral containing a radioactive substance and a powder of an electron generating substance that generates electrons by alpha rays emitted from the natural mineral; A cylindrical magnet body having a north pole at one end and a south pole at the other end. The substance activating member is configured by filling the substance activating material inside the cylindrical magnet body.

2. The powder of the electron generating material is a powder of titanium dioxide, 2. The material activating member according to claim 1, further comprising at least one powder selected from the group consisting of lanthanum hexaboride, black silica, metallic magnesium, tungsten, metallic silicon, molybdenum disulfide, and metallic germanium.

3. 3. The material activating member according to claim 1, wherein an electrode portion is connected to the one end of the cylindrical magnet body which is a north pole side.

4. 4. The material activating member according to claim 3, wherein the electrode portion is a plate electrode connected over the entire end face of the one end of the magnet body.

5. 5. The material activating member according to claim 4, wherein the plate electrode is formed to have an area larger than an area surrounded by an outer circumferential outline of one end of the magnet body.

Citation Information

Patent Citations

  • Combustion activation sheet

    JP2009180191A

  • Material activating device

    JP2009191852A

  • Flammability improving composition material and composition

    JP2010121608A

  • Producing method of sticking sheet in which substance activating material is applied on its surface

    JP2015168737A

  • Antistatic material installed inside the fuel tank

    JP3155020U